PAK signaling in cancer - Diana Zi Ye; Jeffrey Field (2012)
Transformation of a normal cell to a cancer cell is caused by mutations in genes that regulate proliferation, apoptosis, and invasion. Small GTPases such as Ras, Rho, Rac and Cdc42 orchestrate many of the signals that are required for malignant transformation. The p21-activated kinases (PAKs) are effectors of Rac and Cdc42. PAKs are a family of serine/threonine protein kinases comprised of six isoforms (PAK1-6), and they play important roles in cytoskeletal dynamics, cell survival and proliferation. They act as key signal transducers in several cancer signaling pathways, including Ras, Raf, NFκB, Akt, Bad and p53. Although PAKs are not mutated in cancers, they are overexpressed, hyperactivated or amplified in several human tumors and their role in cell transformation make them attractive therapeutic targets. This review discusses the evidence that PAK is important for cell transformation and some key signaling pathways it regulates. This review primarily discusses Group I PAKs (PAK1, PAK2 and PAK3) as Group II PAKs (PAK4, PAK5 and PAK6) are discussed elsewhere in this issue (by Minden).